The idea of women in fundamentalist Islam - Shehadeh, Lamia Rustum, 1940-; NetLibrary, Inc. (Gainesville : University Press of Florida, 2003)
This book deconstructs the religio-political writings and political practices of the nine Islamic ideologues of the twentieth century who masterminded the resurgence of Islamic fundamentalism: Hasan al-Banna, Abu al-'A'la al-Mawdudi, Sayyid Qutb, Ayatollah Ruhollah Khomeini, Ayatollah Mortaza Mutahhari, Zaynab al-Ghazali, Hasan al-Turabi, Rashid al-Ghannoushi, and Sheikh Hussein Fadlallah. It demonstrates that although these ideologues have individual peculiarities, their consistent emphasis on the subordinate status of women in society and in their relation to men constitutes a vehicle for attaining political power. Examining the spectrum of 20th-century Islamic fundamentalist discourse on the subordinate role of women, Shehadeh builds a bridge between political ideology and gender theory. She determines how the diversity of political, social, and economic domains within the discourse of the nine ideologues--male or female, Sunni or Shi'ite, radical or moderate--applies to gender relations, and whether their discourse is distinctive or remains within the classical or traditional mold of Islam. She demonstrates that the importance given to gender issues by fundamentalist ideologues and the constraints imposed on women in society are not so much due to patriarchy as to the manipulation of such issues for purely political purposes--to assure overwhelming male support and to divert attention from the real problems of society.
Hasan al-Banna -- Abu al-'A'la al-Mawdudi -- Sayyid Qutb -- Ayatollah Ruhollah Khomeini -- Ayatollah Mortaza Mutahhari -- Zaynab al-Ghazali -- Hasan al-Turabi -- Rashid al-Ghannoushi -- Sheikh Hussein Fadlallah.
Includes bibliographical references (p. [283]-314) and index.
Electronic reproduction.
Keywords: Women in Islam; Women -- Islamic countries -- Social conditions; Women -- Religious aspects -- Islam; Feminism -- Religious aspects -- Islam; Islamic fundamentalism; Islam; Fundamentalisme; Vrouwen; Electronic books